AN EVALUATION OF FREE AMINO ACIDS AND MINERAL CONTENTS LOCAL EDIBLE MUSHROOMS - ALOFE, F.V. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Free amino acids and minerals (aluminum, potassium, and sodium) of three edibe wild mushrooms. Termitomyses robustus, Trichioma labayensis and Volvariella esculenta, were determined. Twenty-one (21) free amino acids were found in the sample of two of the mushrooms. Phenylalanine was absent while glutamine was found in trace amounts in the stem of T. lobayensis. Most of the free amino acids were present in relatively high concentration. Tryptophan, which ranges between 15.75 and 75.60mg/g, predominated. Aluminum was relatively abundant in all the samples, but all the samples were very low in sodium (range 0.18 to 0.27mg/100g)